Farmer Household Livelihood Strategy Around Karst Area in Tuban, East Java - Widodo, Slamet; Hidayat, Kliwon; Sukesi, Keppi; Yuliati, Yayuk (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2024)
Karst plays an important role in ecology. However, currently, karst areas in Indonesia are experiencing vulnerability. This study aims to examine the livelihood strategies of households around the karst area. The research was conducted in Leran Wetan Village, Palang District, Tuban Regency. This research uses a qualitative approach with a case study method. This research seeks to complement the Sustainable Lifelihood Framework by using the concept of habitus presented by Bourdieu. The main livelihood strategy of the community remains linked to the agricultural sector, especially as farmers or farm laborers, although agricultural mechanization and traditional institutional changes have occurred. Ecological vulnerabilities, such as flooding, trigger changes in livelihood strategies, including working in other sectors. Although there are limestone mines as a new source of livelihood, they are only enjoyed by a small part of the community. The livelihood strategy taken is influenced by the social construction of actors in interpreting karst areas. These findings further confirm that livelihood strategy is a social practice.